Determinants of disability development in patients with multiple sclerosis - Kara, Fatma; Göl, Mehmet Fatih; Boz, Cavit (Arquivos de Neuro-Psiquiatria, 2021)
Background: Multiple sclerosis (MS) is one of the most common chronic neurological diseases affecting the central nervous system in young adults. Objective: To investigate demographic and clinical factors that are effective in the development of irreversible disability from the onset of MS, and to identify factors that affect the transformation from the relapse-remitting MS (RRMS) phase to the progressive MS (PMS) phase. Methods: Retrospective study on 741 patients who were diagnosed with RRMS and PMS according to the McDonald criteria, and were enrolled into the Turkish MS database of the Department of Neurology MS Polyclinic, at the Faculty of Medicine, Karadeniz Technical University, in Trabzon, Turkey. Kaplan-Meier analysis was used to evaluate the time taken to reach EDSS 4 and EDSS 6 from the onset of disease, and the time taken between EDSS 4 and EDSS 6. Results: Age of onset >40 years; having polysymptomatic-type onset, pyramidal or bladder-intestinal system-related first episode; ≥7 episodes in the first 5 years; and <2 years between the first two episodes were found to be effective for MS patients to reach EDSS 4 and EDSS 6. The demographic and clinical parameters that were effective for progression from EDSS 4 to EDSS 6 were: pyramidal or bladder-intestinal system-related first episode; 4‒6 episodes in the first 5 years; >2 years until start of first treatment; and smoking. Conclusions: Our findings reveal important characteristics of MS patients in our region. However, the associations between these parameters and MS pathophysiology remain to be elucidated.
Keywords: Multiple Sclerosis; Epidemiology; Therapy